Collapse capacity of modular steel buildings subject to module loss scenarios: The role of inter-module connections. (1st May 2020) - Alembagheri, M.; Sharafi, P.; Hajirezaei, R.; Samali, B.
Highlights: Resisting capacity of corner-supported modular steel buildings. Different module loss scenarios through instantaneous removal of different modules. Nonlinear dynamic responses in the context of alternate path method analysis. Collapse mechanisms and failure modes through nonlinear static pushdown analysis. Abstract: In modular buildings made of volumetric units, robust structural action may be established by considering various scenarios for localisation of damage, corresponding to loss of supports at the ground floor, such as notional removal of ground floor modules. This paper studies the role of inter-module connections in resisting capacity of modular steel buildings against gravity-induced progressive collapse scenarios, through removing individual or combinations of entire modules at the ground floor. For this purpose, some typical modular buildings are modelled using the macro-model based finite element method. In order to investigate the role of inter-modular connections solely and separate from the effects of other elements, the modules are assumed volumetric rigid bodies, connected through horizontal and vertical interconnections, which are modelled employing translational axial and shear nonlinear springs. Different module loss scenarios are instantaneously imposed to the building models, and their nonlinear dynamic response is monitored in the context of alternate path method analysis. Then the ultimate collapse capacity of the modular buildings along with the collapse mechanism and failure modes are determined through the nonlinear static pushdown analysis. It is shown that the modular buildings possess considerable collapse resisting capacity and are able to offer high level of robustness compared to their conventional counterparts.